2010
DOI: 10.1080/07347332.2010.498458
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Adjustment of Survivors of Ovarian Cancer Treated for Advanced-Stage Disease

Abstract: This study described the long-term adjustment of 42 ovarian cancer survivors diagnosed with advanced-stage disease with no evidence of recurrence, a mean of 6.1 years postdiagnosis. 64% of survivors' mental health was at or above the norm of medical outpatients (Mental Health Inventory-17). No patients reported post-traumatic stress disorder at a diagnosable level (Post-Traumatic Stress Disorder (PTSD) Checklist-Civilian). The majority of survivors (> or = 75%) reported a positive impact of cancer on their liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 29 publications
4
39
0
Order By: Relevance
“…Several other studies have examined demographic and clinical variables in relation to HRQOL in ovarian cancer survivors, with the majority using either the Functional Assessment of Cancer Treatment – Ovarian (FACT-O) or the EORTC QLQ-C30 [6, 7, 10, 11, 16, 18, 20-22, 26]. Similar to our study, older age at diagnosis was found to be associated with poorer functional well-being [18, 20], but better emotional well-being [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies have examined demographic and clinical variables in relation to HRQOL in ovarian cancer survivors, with the majority using either the Functional Assessment of Cancer Treatment – Ovarian (FACT-O) or the EORTC QLQ-C30 [6, 7, 10, 11, 16, 18, 20-22, 26]. Similar to our study, older age at diagnosis was found to be associated with poorer functional well-being [18, 20], but better emotional well-being [20].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the studies either had small sample sizes [4-14] or evaluated mixed samples of gynecologic cancer survivors [7, 15-23]. Most of the existing studies described HRQOL of long-term ovarian cancer survivors at least five years post-diagnosis [6, 9-11, 15-17, 20, 24-26] or solely examined HRQOL of women undergoing active treatment [5, 7, 13, 19, 27, 28]. There are limited data on HRQOL among short-term ovarian cancer survivors (one-to-two years post-diagnosis), with a handful of small studies that assessed HRQOL longitudinally including assessments one-year post-diagnosis [4, 13, 14, 18, 23, 29].…”
Section: Introductionmentioning
confidence: 99%
“…Ersek et al (1997) found that the scores on the quality of life instrument remained moderately high for the ovarian cancer patients, "despite some negative facets of the illness and treatment experience". In other studies, ovarian cancer patients also reported relatively good quality of life when compared with the general population (Kornblith et al, 2010;von Gruenigen et al, 2010). In this study, spiritual well-being of women was found highest among the other sub-scales of quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Spiritual well-being is positively associated with personal growth and ability to integrate the cancer experience (Wenzel et al, 2002). Woman with ovarian cancer also reported that spirituality helped them discern meaning from their cancer experience and maintain hope, and that their faith was important to them as it brought comfort and strength (Kornblith et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Only 10% of a small sample of long-term survivors of stages III to IV OC without evidence of recurrent disease reported functional limitations. 19 In contrast, impaired physical function was reported by 38% of more than 5000 gynecological cancer survivors, which included 922 OC survivors, at least 1 year since diagnosis. Participants were considered functionally impaired if they responded yes to 1 or both questions regarding limitations in activities and use of special equipment due to health problems.…”
Section: Physical Fitness and Functionmentioning
confidence: 98%